Pancasila Sebagai Filsafat Kenegaraan Islami - Tobibatussa’adah Tobibatussa’adah (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
Discussions about Islam and Pancasila are always accompanied by a slightly sensitive nuance. Sometimes there are contents that contain conflict and lead to political action in a certain direction. Even since the beginning of independence, this dialectic gave rise to a long enough dispute, almost a stumbling block to Indonesia's independence. Can not be denied until now, the theme is also still often discussed. Armed with that, this article unravels the study of Pancasila with philosophical reasoning, which is to see internal and external factors that affect it. It appears that the birth of Pancasila based on the excavation of the nation will characterize the heritage and heritage of Indonesia. Moreover, the external conditions that are being overwhelmed by the fear of the tragedy of the collapse of the Islamic Caliphate and the World War. So Pancasila is present as a basic alternative to a country that tries to be neutral and contains local content. It also confirms Indonesian Muslims to become Islamic Nationalists.